2019
DOI: 10.1371/journal.pbio.3000266
|View full text |Cite
|
Sign up to set email alerts
|

Cell aging preserves cellular immortality in the presence of lethal levels of damage

Abstract: Cellular aging, a progressive functional decline driven by damage accumulation, often culminates in the mortality of a cell lineage. Certain lineages, however, are able to sustain longlasting immortality, as prominently exemplified by stem cells. Here, we show that Escherichia coli cell lineages exhibit comparable patterns of mortality and immortality. Through single-cell microscopy and microfluidic techniques, we find that these patterns are explained by the dynamics of damage accumulation and asymmetric part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…The correlation between elongation rate and fluorescence is consistent with early reports that show positive correlations between ribosome levels, which produce proteins, and growth rate [29,34]. It is also consistent with figures 4 and 5 that show that asymmetry between daughter cells is always higher when originating from old mothers, which allocate more of the damaged proteins to her old daughter [18] and more newly synthesized proteins to her new daughter.…”
Section: (E) Correlation Between Green Fluorescent Protein Fluorescensupporting
confidence: 90%
See 3 more Smart Citations
“…The correlation between elongation rate and fluorescence is consistent with early reports that show positive correlations between ribosome levels, which produce proteins, and growth rate [29,34]. It is also consistent with figures 4 and 5 that show that asymmetry between daughter cells is always higher when originating from old mothers, which allocate more of the damaged proteins to her old daughter [18] and more newly synthesized proteins to her new daughter.…”
Section: (E) Correlation Between Green Fluorescent Protein Fluorescensupporting
confidence: 90%
“…In other words--the more different the poles, the more different the daughters. Thus, a substantial proportion of the variation of expressed gene products previously attributed to stochasticity in single E. coli cells results from the deterministic Because elongation rates in E. coli have a deterministic asymmetric component of variance [17,18], the cells quantified for fluorescence in figure 4 were further examined to determine whether they manifested a similar asymmetry and variance pattern for elongation rates and whether GFP and elongation rates were correlated. Elongation rates were measured (see Material and Methods) for all daughters and grouped by old and new mothers.…”
Section: (C) Deterministic Asymmetry Accounts For a Large Component Omentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we neglect damage that had not been repaired before segregation or that would be prohibitively expensive to repair, since the work of Lin Chao’s group has covered this well. They have shown that damage segregation under constant environmental conditions leads to separate steady-state levels of damage in cells of both old and young lineages, meaning that growth rate and mortality of cells do not change over divisions ( 42 , 43 , 94 97 ). (Since there is no trend of deterioration and the replication of young and old lineages does not fit a germline-soma distinction, it is probably better to refer to this as damage homeostasis rather than senescence.)…”
Section: Discussionmentioning
confidence: 99%